Evaluating Parent Satisfaction: The Impact of Educational Service Quality at an Islamic Kindergarten in Colomadu, Karanganyar, Central Java - Eko Purbiyanto; Purwanto Purwanto; Retno Wahyuningsih (STAI Hubbulwathan Duri, 2023)
It is a requirement for every educational institution to engage in self-assessment, and one way to do this is by conducting a survey to assess parents’ perspectives on the teaching and learning experiences their children have undergone. The purpose of this research is to analyze the level of satisfaction of parents of students with the learning process by using the five dimensions of the SERVQUAL variable as the independent variable and consumer satisfaction as the dependent variable. The total population is 70 respondents using census techniques and using a questionnaire to obtain data. The results of this research process indicate that reliability is significant for customer satisfaction with a value of β= 0.198 and is significant at the 0.014 level. Responsiveness is significant to consumer satisfaction with a value of β=0.191 and is significant at the 0.031 level. Assurance is significant to customer satisfaction with a value of β =0.357 and is significant at the 0.005 level. Empathy is significant for consumer satisfaction with a value of β = 0.179 and is significant at the 0.033 level. Tangible positive is not significant to consumer satisfaction with a value of β = 0.001 and not significant at the level of 0.869. SERVQUAL variable f test with customer satisfaction shows a significant effect simultaneously on evidence with an f value of 31.659. And the contribution value of the influence of five SERVQUAL variables on customer satisfaction with the adjusted r square results of 69% and 31% the influence of other variables not examined. In conclusion, tangible has a low and insignificant effect. Suggestions to Islamic Kindergarten in Colomadu Karanganyar, to add teachers and school facilities so that consumer satisfaction increases.